Avatar, the last airbender. Imbalance - Hicks, Faith Erin; Konietzko, Bryan; DiMartino, Michael Dante (Dark Horse Books., 2020)
"When Aang, Katara, Sokka, and Toph return to Earthen Fire Industries-the factory owned by Toph's father-Aang is surprised when their arrival is met with a cold shoulder. As soon as the team is asked for help at a business council meeting, the reason for the slight becomes clear: a massive bender-versus-non-bender conflict has gripped the town and is threatening to turn violent. In order to heal the divide and save the town, Aang and the team will all face tough decisions about power and identity that could tear them apart". -- Publisher annotation.